E-LEARNING, VIRTUAL LEARNING AND SOCIAL CAPITAL - Gavaldon-Hernandez, Guillermina; Azqueta, Diego (PEOPLE: International Journal of Social Sciences, 2017)
E-learning opens new possibilities that may enhance the efficiency with which conventional education reaches its objectives. This is reflectedin the fact that, in general,the returns to investment in human capital, both at the individual and the social level, are increasedwith the help of e-learning. Whereas the impact of e-learningon the acquisition of human capital seems, therefore, to be positive, the same cannot be said with the same level of confidence regarding the acquisition of social capital.As it is arguedin this paper, the impact of e-learningonsocial capital at primary education, when developed as a substitute forthe conventional school(distant e-learning) may well be negative. Taking into account the importance of some components of social capital with regard to the benefits of education, also from an economic point of view, the introduction of distant e-learningshould not be donein an uncritical manner, but after a careful analysis of its impact onsocial capital.At graduate levels, however, e-learning provides an interesting kind of social capital worth analysingin some more detail.